Brainstem catecholaminergic neurones and breathing control during postnatal development in male and female rats - Patrone, Luis Gustavo A. (J Physiol, 2018)
KEY POINTS: The brainstem catecholaminergic (CA) modulation on ventilation changes with development. We determined the role of the brainstem CA system in ventilatory control under normocapnic and hypercapnic conditions during different phases of development [postnatal day (P)7–8, P14–15 and P20–21] in male and female Wistar rats. Brainstem CA neurones produce a tonic inhibitory drive that affects breathing frequency in P7–8 rats and provide an inhibitory drive during hypercapnic conditions in both males and females at P7–8 and P14–15. In pre‐pubertal rats, brainstem CA neurones become excitatory for the CO(2) ventilatory response in males but remain inhibitory in females. Diseases such as sudden infant death syndrome, congenital central hypoventilation syndrome and Rett syndrome have been associated with abnormalities in the functioning of CA neurones; therefore, the results of the present study contribute to a better understanding of this system. ABSTRACT: The respiratory network undergoes significant development during the postnatal phase, including the maturation of the catecholaminergic (CA) system. However, postnatal development of this network and its effect on the control of pulmonary ventilation ([Formula: see text]) is not fully understood. We investigated the involvement of brainstem CA neurones in respiratory control during postnatal development [postnatal day (P)7–8, P14–15 and P20–21], in male and female rats, through chemical injury with conjugated saporin anti‐dopamine β‐hydroxylase (DβH‐SAP). Thus, DβH‐SAP (420 ng μL(−1)), saporin (SAP) or phosphate buffered solution (PBS) was injected into the fourth ventricle of neonatal Wistar rats of both sexes. [Formula: see text] and oxygen consumption were recorded 1 week after the injections in unanaesthetized neonatal and juvenile rats during room air and hypercapnia. The resting ventilation was higher in both male and female P7–8 lesioned rats by 33%, with a decrease in respiratory variability being observed in males. The hypercapnic ventilatory response (HCVR) was altered in male and female lesioned rats at all postnatal ages. At P7–8, the HCVR for males and females was increased by 37% and 30%, respectively. For both sexes at P14–15 rats, the increase in [Formula: see text] during hypercapnia was 37% higher for lesioned rats. A sex‐specific difference in HCRV was observed at P20–21, with lesioned males showing a 33% decrease, and lesioned females showing an increase of 33%. We conclude that brainstem CA neurones exert a tonic inhibitory effect on [Formula: see text] in the early postnatal days of the life of a rat, increase variability in P7–8 males and modulate HCRV during the postnatal phase.